The European Synarchy: New Discourses on Sovereignty - Dimitris N. Chryssochoou (Göttingen Journal of International Law)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText {margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:21.25pt; margin-bottom:.0001pt; text-align:justify; text-indent:-21.25pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} span.MsoFootnoteReference {mso-style-noshow:yes; vertical-align:super;} p.ArticleText, li.ArticleText, div.ArticleText {mso-style-name:"Article Text"; mso-style-update:auto; margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:1.0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} /* Page Definitions */ @page {mso-footnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fs; mso-footnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fcs; mso-endnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") es; mso-endnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") ecs;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Half a century since its inception as a community of western European democracies, limited in scope and competences, the European Union (EU) is taken to denote a composite polity that combines unity and multiplicity while having the capacity to produce publicly binding decisions and allocate values in European society. It is thus possible to capture the endemic systemic complexity of the regional process through the lens of new theoretical perspectives with a view to developing a series of novel understandings of EU governance in the early twenty-first century. So far, the EU polity refers to a system of institutionalized shared rule among multiple state and non-state actors, characterized by the dispersal of political authority among various levels and the transcendence of hierarchical forms of power distribution. Thus different notions of democracy, legitimacy and representation produce novel accounts of post-national politics. Accordingly, a new democratic concept for the EU project should entail a balanced mix of social and political forces that share in the emerging sovereignty of the larger unit. Within the latter, public authority should not reside within a single decision-making centre, but rather should be diffused among different governance levels and forms of social, political and cultural contention that can combine territorial and substantive public issues. At the same time, recent changes in the workings of the EU polity have not affected its nature as an essentially statecentric project, preserving a balance between state sovereignty and a relatively moderate yet discernible deepening of integration by means of producing a system of political co-determination; in other words, a new form of synarchy between states and demoi – an ensemble sui generis of highly interdependent systems – is created, its structural and functional interaction resulting in a multilogical system of entwined sovereignties.<!--[if !supportFootnotes]-->[1]<!--[endif]--> Yet, the EU polity still remains a treaty-constituted body politic and not the unilateral act of a single and undifferentiated demos. Moreover, it does not derive its political authority from its citizens directly and has not – as yet – resulted in a complete fusion among different levels of public authority. Also, its constituent parts, in the form of historically constituted nation-states, are free to dissociate themselves from the larger unit. Finally, its emerging yet nebulous and even controversial constitutional identity rests heavily on the domestic orders of states, although the EU already projects a profound intertwining of democracies regarding the joint exercise of fundamental powers. Arguably, all of the above is crucial to understanding the changing conventions regarding state sovereignty that may now be interpreted as the right to be involved in the joint exercise of competences with other states. Linked to the question of sovereignty is that of democracy, which currently points to a negative side-effect of European integration: the growing dissonance between the requisites of democratic rule and the actual conditions on which the political management of EU affairs is largely based. The crucial distinction here concerns an institutional and a socio-psychological perspective. Whereas the former focuses on power-sharing and on institutional reform as a solution to the actual or perceived problems of democracy in the EU, the latter is concerned with questions of European identity and the formation of a composite European demos that is nonetheless distinct as a collectivity. As the current debate raises fundamental questions about the future form of the EU as a polity of highly interrelated states and demoi – a synarchy of entwined sovereignties – recent reforms, including the Lisbon Treaty<!--[if !supportFootnotes]-->[2]<!--[endif]-->, whose ratification is still pending, failed to enhance the democratic properties of the general system, leaving the EU to resemble a system of democracies more than a democratic system in its own right. In a period when transnational pressures are challenging both intrastate and interstate relations, it may no longer be enough to confine democracy within state boundaries to deal effectively with the implications of new forms of polity. This raises new questions such as how to hold transnational decision-makers to account to citizens who belong to different national political systems. Such questions reflect substantive concerns that have grown as the regional process has evolved from an interstate diplomatic forum to a fully-fledged polity. This development, otherwise known as a “normative turn” in EU studies, has led to scholarly interest in the idea that the EU might one day transform itself into a democratic political system. While there is some measure of agreement that the EU is not democratic, there is no consensus on how it might become so. Indeed, there are two different understandings of what the EU’s democratic deficit comprises. The first focuses on institutional properties, arguing that the problem of democracy in the EU is tied to the flawed interinstitutional interactions that characterize the functioning of a non-state polity like the EU. In this context, proposals for further reform speak of the EU’s ”institutional imbalance” and of the need to enhance the public accountability as well as the representative nature of EU policy-makers and decision-takers. The second focuses on sociopsychological factors and makes the case for a new sense of European “demos-hood”. It argues that the EU’s present democratic pathology occurs because of the absence of a European demos. As a consequence, this second perspective is more interested in collective civic identity and the extent to which there is “a feeling of community” amongst Europeans. Acknowledging that the absence of a European demos – assuming that a legal or economic demos already exists – is a barrier to a democratic Europe, proposals for further reform tend to suggest paths to transnational demos-formation based on a common European civicness<!--[if !supportFootnotes]-->[3]<!--[endif]-->. These notions of plural citizenship give rise to the idea of a “Republic of Europeans”, to which we now turn. <!--[if !supportFootnotes]--> <!--[endif]--> <!--[if !supportFootnotes]-->[1]<!--[endif]--> Dimitris N. Chryssochoou, Theorizing European Integration, 2nd ed. (2009). <!--[if !supportFootnotes]-->[2]<!--[endif]--> Treaty of Lisbon amending the Treaty on European Union and the Treaty establishing the European Community, 13 December 2007, OJ 2007/C 306/01. <!--[if !supportFootnotes]-->[3]<!--[endif]--> Dimitris N. Chryssochoou, Democracy in the European Union (1998).